Analysis of the ground surface finish effect on the LCF life of a 304L austenitic stainless steel in air and in PWR environment. (November 2017) - Poulain, T.; Mendez, J.; Hénaff, G.; de Baglion, L.
Highlights: Low Cycle Fatigue life of a 304L stainless steel in PWR environment is shorter than in air at 300 °C. The strain intensity factor ΔKε accounts for the crack front shape in ground and polished samples. Fatigue crack growth laws were established in polished samples in each environment. The crack growth rates can be obtained from striation spacing in PWR environment but not in air. The propagation life in ground specimens is predicted in both environments. Abstract: In this paper, the Low-Cycle Fatigue (LCF) resistance of an austenitic 304L stainless steel used in nuclear plant components is investigated. More precisely, a special attention is here paid to the respective role of surface finishing and environmental effects on the elementary damage stages, namely crack initiation and crack propagation. The objective is not only to assess the conservatism of design rules introducing corrections factors to account for the decay induced by these parameters, but also to get insights into the mechanisms controlling the fatigue life. With this aim, fatigue tests are performed under a controlled total strain amplitude Δεt /2 of 0.6% with a strain rate of 10 −4  s −1 on ground or polished cylindrical specimens, in air and in Pressurized Water Reactor (PWR) environment. A detailed analysis of surface damage and fracture surfaces is conducted to estimate the respective fraction of initiation and propagation in the total life according to the environment and surface finishing. It first comes out that, regardless of the considered condition, the initiation stage is negligible with respect to the propagation duration. Furthermore, it is shown that the propagation in ground specimen is affected, in both environments by the specific crack shape resulting from the initiation process and subsequent coalescence of multiple initiated cracks within the grinding scratches. Moreover, a detailed analysis of striations present on fracture surfaces indicates that while a good correlation between the striation spacing and the average crack growth rate is noticed in PWR environment, a discrepancy is observed in air. Nevertheless LCF crack growth laws have been identified is each environment by introducing the strain intensity factor ΔKε . It is then demonstrated that predictions of fatigue life carried out by accounting for the initial surface finishing through the crack shape factor and the environmental effect by means of the proper crack growth law present a good agreement with experimental data.